Regional disparity in age-related disability: toward healthy aging in Indonesia - Puspitasari, Mardiana Dwi; Rahardja, Mugia Bayu; Nurhayati, Septi; Surbakti, Indra Murty (BKM Public Health and Community Medicine, 2024)
Purpose: Maintaining functional ability and minimizing age-related disability of older adults are required to promote healthy aging. A supportive physical and social environment, in addition to individual variables, has a role in reducing the risk of age-related disability. Infrastructure development differs between Java-Bali and outer Java-Bali regions. This study aims to determine the extent to which the disability of older adults in Java-Bali and outer Java-Bali regions. Methods: This study is cross-sectional, using data from the 2020 National Socio-Economic Survey (SUSENAS) with 122.344 Indonesian older adults aged 60 and over. Disability is the outcome variable. The explanatory variable is regional disparity (Java-Bali and outer Java-Bali regions), which refers to where the older adults live. In addition, the control variables include age, sex, marital status, educational level, employment status, leisure activity, household wealth status, and self-rated health status (SRHS). A multivariate logistic regression statistical analysis is performed. Results: The outer Java-Bali region has a slightly greater prevalence of older adults with age-related disability than the Java-Bali region, with 28.8 and 22.9 percent, respectively. However, older adults living in the outer Java-Bali region are 1.63 times more likely (OR 1.63; 95% CI (1.58-1.68)) to have disability than those living in the Java-Bali region. Other socio-demographic variables are significantly associated with age-related disability. Conclusion: Living in the Java-Bali region increases the risk of age-related disability. Infrastructure development in the outer Java-Bali region needs to be improved so that older adults can experience healthy aging.